HUBUNGAN MOTIVASI DENGAN TINDAKAN PAP SMEAR PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS - Widiani, Komang Sri (Coping: Community of Publishing in Nursing; Vol 2 No 3 (2014): JURNAL EDISI SEPTEMBER-DESEMBER 2014, 2014)
Cervical cancer is stated as the second cause of death of woman worldwide. An increased risk of cervical cancer every year is a serious threat for woman which highly related to their reproduction health. Short of awareness and less motivation to follow "pap smear" examination caused by several factors. This research aims to find out the relation between motivation and "pap smear" examination to woman of childbearing age. This research uses corelational with cross sectional approaching technique. Specimen election in purposive sampling with 108 respondents involved. Data collection by using questionnaire.The result of this research shows that among 108 childbearing age woman (CAW), there is 1 (4,7 %) who have high motivation and have done "pap smear" examination. 20 of respondents (16,3 %) CAW has high motivation but havent done any "pap smears " examination. Another 23 respondents (19,3%) CAW have average motivation and have done "pap smears" examination. The rest 64 respondents (67,7%)CAW have average motivation and have not done any "pap smear" examination. And none od CAW with low motivation and ever or never do "pap smear" examination.The result of chi-square significantly shows P value 0.032 with (alfa = 0.5), so there is relation between motivation and "pap smear" examination to woman of childbearing age.In accordance to the result of this research, it is highly suggested to medical person to promote any programs that encourage and motivate childbearing age woman to do a 'pap smear" examination and increasing woman of childbearing age's knowledge who actively doing sexual intercourse to so "pap smear" examination.
Keywords: Motivation, Pap Smear Examination, Childbearing Age Woman.